Chosen Elements of Civilizational Selection Theory This is Why Unwilling Events Are Unavoidable - Wolanin, Jerzy M. (Communications - Scientific letters of the University of Zilina, 2006)
Man has always lived in two spaces, natural environment and civilizational space. Civilizational space has been formed by man, is built up of all human activities, and has been created among others as human response to hazards. Variability of civilizational space causes the necessity of keeping up with changes. Things that were good yesterday today are of no value, which means they no longer protect from unwilling events. Description delay in relation to its constant change in civilizational space along with its complexity causes difference in interpretation. Occurrence of unwilling event is a sign that the accepted solution was bad and needs improvement. Thus, civilizational space is a source of hazards.